Dragon kingdom of Wrenly. Book 6, Ice dragon - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2021)
Ruskin and his friends travel to Flatfrost for the Winter Festival where the legendary ice dragon has appeared -- she who unknowingly holds an important piece to the puzzle of who are the dark forces are that have been plotting against Ruskin all along.